Enriching the Students Vocabulary Mastery in Speaking through Engage, Study, Activate Method - Agus Rahmat (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2019)
The objectives of this research are to find out the improvement of students’ vocabulary mastery and the student’s activeness in speaking through Engage, Study and Activate Method at the second year students of SMP Negeri 26Makassar. This research used Classroom Action Research that comprises of two cycles. The research population is the second year students of SMP Negeri 26 Makassar, and the sample of this research comprises of 25 students. The researcher obtained the data by using a speaking test and observation sheet.The results of this research show that there is animprovement in students' vocabularybetween the cycle I and Cycle II. The mean scores of students in the diagnostic test are 4.7 became 6.21 in cycle I, and after doing a revision in the cycle II the mean score in cycle II is7.45 then the activeness of students also improve from first meeting 53 % became 92% in the last meeting and achieved the minimal criteria, 65. The research findings indicate that the use of Engage, Study and Activate method can enrich the students’ vocabulary mastery and improve the students’ activeness in speaking.